2022
DOI: 10.1210/clinem/dgac679
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual Variability of Serum Aldosterone and Implications for Primary Aldosteronism Screening

Abstract: Context Primary aldosteronism (PA) screening relies on an elevated aldosterone to renin ratio with a minimum aldosterone level, which varies from 10 to 15 ng/dL (277 to 415.5 pmol/L) using immunoassay. Aim To evaluate intraindividual coefficient of variation (CV) of aldosterone and aldosterone to direct renin concentration ratio (A/DRC) and its impact on PA screening. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…The algorithm for PA investigation followed the 2016 Endocrine Society Guideline for PA management [2]. In our Institution, a positive screening for PA, defined as an aldosterone/DRC ratio > 2 ng/ dl/μIU/ml (or 55.5 pmol/l/μIU/ml) with concomitant aldosterone levels > 10 ng/dl (or 277 pmol/l), has a true positive rate of 95 % for PA diagnosis [23].…”
Section: Methodsmentioning
confidence: 99%
“…The algorithm for PA investigation followed the 2016 Endocrine Society Guideline for PA management [2]. In our Institution, a positive screening for PA, defined as an aldosterone/DRC ratio > 2 ng/ dl/μIU/ml (or 55.5 pmol/l/μIU/ml) with concomitant aldosterone levels > 10 ng/dl (or 277 pmol/l), has a true positive rate of 95 % for PA diagnosis [23].…”
Section: Methodsmentioning
confidence: 99%
“…[12] Less stringent criteria increase the detection rates of both advanced and mild forms of PA. [26][27][28][29] Two recent systematic reviews of ARR testing found that the clinical performance of ARR varied widely with the patient population, clinical setting, and thresholds used, rendering sensitivities from 10% to 100%. [30,31] Considering the dynamic fluctuations of renin and aldosterone in response to a large number of determinants, [32][33][34] the current Endocrine Society guideline proposes confirmatory testing in most patients with positive screening results in order to solidify the PA diagnosis. [12] Notably, however PA has been diagnosed in individuals with ARR values lower than the commonly used threshold for PA, indicating the limitations of arbitrary screening criteria in capturing the broad continuum of inappropriate aldosterone production.…”
Section: The Evolving Definition Of Pamentioning
confidence: 99%
“…Considering the dynamic fluctuations of renin and aldosterone in response to a large number of determinants [32][33][34], the current Endocrine Society guideline proposes confirmatory testing in most patients with positive screening results to solidify the PA diagnosis [12]. Notably, however, PA has been diagnosed in individuals with ARR values lower than the commonly used threshold for PA, indicating the limitations of arbitrary screening criteria in capturing the broad continuum of inappropriate aldosterone production.…”
Section: The Evolving Definition Of Primary Aldosteronismmentioning
confidence: 99%
“…Nesse cenário, o valor de corte de 10 µU/mL no tempo de 2 horas aumentou a sensibilidade e especificidade para o diagnóstico de HP. Embora, essa conclusão seja preliminar, já que somente 6 casos com HA com renina suprimida foram analisados, foi considerado o valor de corte de renina de 10 µU/mL como o mais adequado para o TFO no tempo 2 horas.Recentemente, diversos estudos demonstraram uma importante variabilidade intraindividual nos valores de aldosterona basais em pacientes com HP15,64 . Yozamp et al64 mostraram que aproximadamente 30% dos pacientes com HP tiveram pelos menos um valor de aldosterona <10 ng/dL e 50% dos pacientes pelo menos um valor de aldosterona <15 ng/dL.…”
unclassified